How to prepare for the TOEFL test : test of English as a foreign language - Shape, Palmela J., Ph. D.; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2003)
Introduction; Questions and answers concerning the toefl; Review of section 1: listening; Review of section 2: structure; Review of section 3: reading; Review of writing essays; Toefl model tests; Answer keys for the toefl review exercises and model tests; Explanatory answers for the Toefl model tests; Transcript for the listening sections of the toefl model tests; Featured colleges and universities.
Keywords: Anh ngữ; English language; Toefl; English language -- Study and teaching; English language -- Tests